Medical Education in Infectious Diseases. Using Smartphone Apps for Active Learning - Valdez, Luis (2017)
Background Active Learning using smartphone technology can be implemented as a tool for teaching medical students (MS) and residents (Rs). The use of technology would increase participation and enhance student learning by engaging them in solving ID clinical case scenarios. Our objective was to describe the methods used and to share the opinions of the users of such active learning methods. Methods The smartphone applications used were Socrative and WhatsApp. We used Socrative during the Universidad Peruana de Ciencias Aplicadas (UPC) ID course for MS in two different ways. In selected lectures (4 of 32), teacher paced questions were asked based on clinical scenarios related to the topic reviewed, and by voluntary homework questionnaires (student paced). At the British American Hospital (BAH) Medicine Department (MS and Rs) Socrative was used similarly: during some noon lectures (teacher paced questions) and during the baseline MS exam and Rs mid-year exam and voluntary homework questions (student paced). WhatsApp is currently used at the BAH with questions send from Monday to Friday. MS /Rs answer individually via WhatsApp to the mentor in charge. The right answer is given the next day. Questions using WhatsApp deal with recent cases seen at the Wards or in the outpatient clinic, and are designed so that the MS/Rs must do quick literature searches in order to provide the right answer. Results Forty-one MS/Rs answered the survey on Socrative use, 25 of 48 (52%) of UPC MS and 16 (89%) MS/Rs from the BAH. Forty (97%) believed using Socrative had influenced their learning and all but 2 believed it promoted participation from the class. 36 (87.8%) would like to have Socrative used in other lectures and 35 (85%) in other courses. Only one person voted against Socrative use in courses or lectures. With regards to WhatsApp use 16 MS/Rs from BAH answered the survey. Six had used before WhatsApp as a teaching tool. All felt the methodology was useful for learning and promoting reading and would recommend this methodology to promote learning on a student paced way. Conclusion Socrative and WhatsApp can be used for teaching ID through MS/Rs smartphones. Most MS/Rs who were surveyed recommended the use of such methods in their education.